Optical properties of quantum dots - Al-Douri, Yarub; Jose, Rajan (Elsevier, 2022)
The full potential-linearized augmented plane wave implemented in WIEN2K code to calculate the indirect energy gap (Γ–X) using density functional theory, thermal evaporation, and chemical bath deposition techniques are employed for analysis and characterization of different elements, compounds, and alloys semiconductors. Theoretically, modern implementations allow for a number of approximations to exchange and correlation and make no approximations to the shape of the crystal potential, unlike methods employing the atomic sphere approximation which assumes spherical symmetry around each atom. Additionally, Engel–Vosko generalized gradient approximation and modified Becke Johnson (mBJ) formalisms are used to optimize the corresponding potential for energetic transition and optical properties calculations as a function of quantum dot diameter to test the validity of our model of quantum dot potential. The refractive index and optical dielectric constant are investigated to explore best applications for solar cells. Experimentally, the structural and optical properties of X-ray diffractometer, ultra-violet (UV-vis), and transmission electron microscopy. The obtained results are in accordance with other experimental and theoretical data.